What is said and unspoken about the autonomy of a nurse: (dis) continuity in discourses - Sabrina Gonçalves Aguiar Soares; Silviamar Camponogara; Mara Ambrosina de Oliveira Vargas (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to know how autonomy is constituted in the nurse's professional practice in the hospital context. Methods: Qualitative analytical study, based on Foucault's methodological theoretical framework. The empirical material consisted of articles published in the Revista Brasileira de Enfermagem and narrative interviews conducted with 18 nurses from a public hospital in southern Brazil. Data collection took place between December 2017 and May 2018, being analyzed through Foucauldian discourse analysis. Results: Autonomy in the professional practice of nurses goes through the core of knowledge, the political positioning and the working conditions. These factors are revealed as power instruments in the construction of nurse governability. Final Considerations: It is believed that the investment focused on the debate of the nurse's autonomy interfaces could raise new attitudes about professional practice and favor the transformation of nursing practice.